Pengaruh Metode Ekspresi Bebas Terhadap Kreativitas Siswa Dalam Menggambar Tiga Dimensi Di Sekolah Dasar - Rahmadani, Suci; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research aims to determine the influence of free expression method on the creativity of students in drawing three dimensions in class IV Elementary School State Gugus 1 IVAngkek subdistrict. This type of research is quantitative research with the method of experimental and design Quasi Exsperiment, with the form of Non-equivalent control group design. The population in this research is the SD State Gugus 1 IVAngkek subdistrict and sample techniques using simple random sampling technique.The data collection techniques used are essay-shaped tests. The data analysis technique used is test-t to see the influence of the two average values after the test of normality and homogeneity test. The results of this study showed that the Meanpost-test class of experimentation was 79.96 and the mean control class 77.00. Analysis of data from both classes obtained thitung results = 5.132 and this = 1.701 at a significant level 0.05 so Thitung >This then ha acceptable. Thus it can be concluded that the free method of expression is positive towards the student's creativity in drawing three dimensions in class IV of State Elementary School Gugus 1 IVAngkek subdistrict.